Novel mutation in ENG gene causing Hereditary Hemorrhagic Telangiectasia in a Peruvian family - Zevallos-Morales, Alejandro (2020)
Hereditary Hemorrhagic Telangiectasia (HHT) is a rare disorder of vascular development. Common manifestations include epistaxis, telangiectasias and arteriovenous malformations (AVMs) in multiple organs. Most patients have deletions or missense mutations in the ENG or ACVRL1 gene respectively, significantly affecting endothelium homeostasis. We analyzed the ENG gene in five members of a Peruvian family affected by HHT. One novel mutation was found in exon four of the ENG gene c.408delA, at aminoacid residue 136. This mutation changes the subsequent reading frame producing an early stop at residue 162, preserving only one fourth of the normal protein of 658 aa. This mutation was found in the four affected members of family.